Dampak Gaya Kepemimpinan, Ketidakpastian Lingkungan, dan Informasi Job-Relevant terhadap Perceived Usefulness Sistem Penganggaran - Susilawati Muslimah (The Indonesian Journal of Accounting Research, 2013)
This study examines the effects of leadership styles, perceived environmental uncertainly, and job-relevant information on budgeting systems. Budgeting systems were defined in terms of the perceived usefulness of several budgeting characteristics that can be related to budgeting systems. These budgetary characteristics were included in budgetary participation, budget goal clarity, budget goal difficulty, budgetary evaluation, and budgetary feedback. In addition to examining the direct effects of independent variables specified, this study sought to determine how the independent variables interacted. Using mail survey of a total 500 managers were drawn from 63 leading companies from the Java island. They were requested to respond to a quetionnaire, 46 of them responded. The data collected was analyzed using a multiple regresion equations and path analysis statistics. The research hypotehses were examined using F and t test on an 5% convidence interval. F tests showed that three of budgetary characteristics were significant. First, budgetary evaluation had F test of 0,04, second, budgetary feedback had F test of 0.003, and finally, budgetary goal difficulties had F test of 0,09. If, t test on an 10% convidence imterval, than budgetary goal difficulty was stated significant.   However, the two other characteristics budgetary participation and budgetary goal clarity were not significant on an interval confidence of 5% or 10%. The t test results in this study indicated that : (1) Leadership styles are associated with the range of budget goal difficulty, budgetary evaluation, and budgetary feedback, perceived environmental uncertainty with the range of budget goal difficulty, and job relevant information with budgetary feedback. (2) The indirect effects of perceived environmental uncertainty acting through leadership style have influence to the range budget goal difficulty.